Metode Muḥāfaẓah Naẓam Jurūmiyyah untuk Memudahkan Baca Kitab Kuning - M Abdul Ghofur; Hafidotul Husniah (INAIFAS PRESS, 2022)
The yellow book is a learning resource that uses Arabic without a vowel and requires special skills to be able to read it. Muḥāfaẓah naẓam Jurūmiyyah method is a way to make it easier for students to read the yellow book. The purpose of this study was to describe the implementation of muḥāfaẓah naẓam Jurūmiyyah method in reading the yellow book in Ponpes As-Sunniyyah Kencong Jember. The results of the research found that with muḥāfaẓah naẓam Jurūmiyyah method, 85% of the research subjects received the predicate of very good value while the remaining 15% had the predicate of good. This research proves that muḥāfaẓah naẓam Jurūmiyyah method is able to make it easy for students to read the yellow book and motivate them to explore Arabic grammar as a basic ability to be able to read the yellow book properly and correctly.